Development, stability and in vitro delivery profile of new loratadine-loaded nanoparticles - Jesus Rafael Rodriguez Amado; Ariadna Lafourcade Prada; Jonatas Lobato Duarte; Hady Keita; Heitor Rivero da Silva; Adriana Maciel Ferreira; Edgar Hernandez Sosa; Jose Carlos Tavares Carvalho (Elsevier, 2017)
Purpose: Loratadine is used as antihistaminic without side effects in nervous systems. This drug is a weak base and it is absorbed from the intestine. The nitrogen of the pyridine ring is protonated in the stomach affecting the oral bioavailability. The aim of this paper was obtaining, characterize and evaluate the release profiles and the stability of a gastroresistant loratadine nanosuspension. Methods: The nanosuspension was prepared by the solvent displacement evaporation method, using three different polymers (Eudragit® L 100 55, Kollicoat® MAE 100P and PEG 4000) and Polysorbate 80. Dynamic Light Scattering was used for evaluating the particle size (PS), zeta potential, and conductivity of the nanosuspension. Loratadine release profiles were evaluated in simulated gastrointestinal fluids. The shelf and accelerated stability were assessed during three months. Results: Nanosuspension particle size was 45.94 ± 0.50 nm, with a low polydispersion index (PdI, 0.300). Kollicoat® MAE 100P produced a hard and flexible coating layer. In simulated intestinal fluids, the 100 percent of loratadine was released in 40 min, while in simulated stomach fluids the release was lesser than 5%. Nanosuspension presented a good physicochemical stability showing a reduction in PS and PdI after three months (43.29 ± 0.16 and 0.250; respectively). Conclusions: A promissory loratadine nanosuspension for loratadine intestinal delivery was obtained, by using a low energy method, which is an advantage for a possible scale up for practical purpose. Keywords: Loratadine, Nanoparticles, Nanosuspension, Zeta potential, DLS, Simulated gastric fluids